Functions of administrative law: the formation of a modern concept - Калюжний, Ростислав Андрійович; Колпаков, Валерій Костянтинович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The monograph by Yu. V. Pirozhkova "Functions of administrative law: genesis, theoretical, normative and praxeological aspects" is reviewed. It is noted that the monograph is devoted to one of the most relevant and interesting theoretical problems of modern legal science, namely the creation of the theory of functions of administrative law. It is one of the first attempts to analyze and characterize the theory of functions of an important legal branch in the context of the transformation of its subject, to identify the main problems of their effective implementation, which allowed us to propose a functional concept of administrative law, to substantiate a number of new theoretical propositions and conclusions, provide practical recommendations and suggestions on the issues under study.